IPTEKS PENGAKUAN PROFITABILITAS PENDAPATAN DAN BEBAN PADA PT. ESTA GROUP JAYA - Thenu, Gilbert; Runtu, Treesje (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Profitability analysis is an efforts to measure the fullest ability of a company to measure profit. Profitability analysis based by two aspects, which is based on income or sales and investment. Analysis of company profitability has the importance of the external party which is stakeholder, so its management must provide financial statements in it including good income and load profitability reports so inviting comfort for stakeholders in seeing companies in profitability management.Keywords : Profitability of income and expenses, Profitability management